Tesis: AUTORES: María Lourdes Díaz-Trechuelo y López-Spinola, Labor Gómez Acevedo, Francisco López Cruz, Delfina Esmeralda López Sarrelengue, M. Peñuelas, A. Janto Stephen (O.F.M.) - autor, Sin (Revista Española de Antropología Americana, 1956)
Sin resumen